Effect Of Constraints On Perceived Business Success Of Rural Entrepreneurial Activities: A Case Of Two Rural Municipalities - Agbenyegah, Albert Tchey (Journal of Applied Business Research, 2017)
This study aims to evaluate the effect of selected entrepreneurial constraints on the perceived business success of small businesses. In this study the dependent variable, perceived business success is measured by two variables; business growth and existence of human capital. A 7 Likert scale structured questionnaires anchored on “1” strongly disagree and “7” strongly agree is used to source data from entrepreneurs. The convenience and snowball technique were used to source 300 entrepreneurs from the target population for data. Reliability of the measuring instrument was possible through the Cronbach alpha while the questionnaire was piloted for conceptual realities. In this study, the precise and individual constraints were operationalized as independent variables. Relationships between the independent variables and the perceived business success as dependent variable were investigated through multiple linear regression analysis. The outcomes of the study resolved that precise and individual constraints impact negatively on the perceived business success of small businesses and entrepreneurial activities. The findings further revealed adverse links between the independent and the dependent variable known as the perceived business success.
Keywords: Perceived Business Success; Precise and Individual Constraints; Entrepreneur; Frances Baard; John Taolo Gaetsewe Municipalities